Imaging Amblyopia: Insights from Optical Coherence Tomography (OCT). (19th May 2019) - Gaier, Eric D.; Gise, Ryan; Heidary, Gena
ABSTRACT: Amblyopia refers to visual impairment resulting from perturbations in visual experience during visual development, typically secondary to strabismus, uncorrected refractive error, and/or deprivation. Amblyopia has traditionally been considered a cortical disease, but the depth of our understanding of this complex neurodevelopmental condition is limited by our ability to appreciate structural pathophysiology in the visual pathway. Recent advances in Optical Coherence Tomography (OCT) have facilitated numerous studies of the structural changes in the retina and optic nerve, thereby expanding our appreciation for the pathogenesis of this condition. In this review, we summarize findings from studies evaluating retinal, retinal nerve fiber layer, and choroidal thickness changes in patients with amblyopia. Focusing on the largest and most recent studies, we discuss common limitations and confounding variables in these studies. We summarize recent advances in ocular imaging technology and reconcile the findings of early histological reports with those of structural OCT in amblyopia.